(untitled) (Journal of Partial Differential Equations, 2019)
In this paper, we are concerned with the existence and uniqueness of mild solution for a class of nonlinear fractional Sobolev-type stochastic differential equations driven by fractional Brownian motion with Hurst parameter H∈(1/2,1) in Hilbert space. We obtain the required result by using semigroup theory, stochastic analysis principle, fractional calculus and Picard iteration techniques with some non-Lipschitz conditions.